The Impact of Mass Bed Net Distribution Programs on Politics : Evidence from Tanzania - Croke, Kevin (World Bank, Washington, DC, 2017)
Functioning democracy requires that citizens reward politicians who deliver benefits, yet there is surprisingly little causal evidence of changes in citizen views or behavior in response to specific government programs. This question is examined in Tanzania, which has recently implemented large health programs targeting diseases such as HIV/AIDS and malaria. Tanzania's 2010-2011 national anti-malaria campaign took place concurrently with a national household survey, which enables a regression discontinuity design based on interview date to estimate the effect of this program on the popularity of local politicians. Bed net distribution results in large, statistically significant improvements in the approval levels of political leaders, especially in malaria endemic areas. Effects are largest shortly after program implementation, but smaller effects persist for up to six months. These findings suggest that citizens update their evaluation of politicians in response to programs, especially when these services address important problems, and that the effects decay over time, but not completely.